The Impact of Combined Problem-Based Learning and Teams Games Tournament on Student Motivation and Academic Achievement - Tita, Ninda Julia; Farida Agus Setiawati; Lusiana, Nunung; Intansari, Ilfi (International Journal of Elementary Education, 2024)
Improving the quality of classroom learning is crucial in addressing issues related to low motivation and academic achievement among students. Based on observations, the classroom learning process is still considered boring and lacks direct student engagement, which leads to low motivation and suboptimal learning outcomes. This study aims to analyze the effect of using a combined method to improve motivation and academic achievement separately. The study uses a quasi-experimental quantitative method with an experimental design. Sampling was carried out using purposive random sampling, dividing the sample into two groups: the experimental class and the control class. Data were collected through tests and questionnaires, and data analysis was conducted using ANOVA. The results showed that in the academic achievement variable, there was a significant difference between the two classes, with a significance value of 0.000, which is smaller than the alpha value of 0.05. The mean score of the experimental class was 83, while the control class had a mean of 75. In the motivation variable, the results also showed a significant difference in means, with a significance value of 0.000. In conclusion, the use of the combined Problem-Based Learning (PBL) and Teams Games Tournament (TGT) models is proven to be effective in improving academic achievement and motivation separately.